Expression and roles of CCN2 in dental mesenchymal cells in primary culture—With findings in a case of odontogenic myxofibroma. Issue 1 (29th March 2013) - Shimo, Tsuyoshi; Koyama, Eiki; Horikiri, Yuu; Okui, Tatsuo; Kurio, Naito; Katase, Naoki; Yoshida, Shoko; Takebe, Yuichiro; Kishimoto, Koji; Yoshioka, Norie; Nagatsuka, Hitoshi; Sasaki, Akira
Abstract: Purpose of the research: Tooth germ development involves multiple events, including cell proliferation and cell differentiation. Connective tissue growth factor (CTGF/CCN2) is a signaling protein involved in tooth germ development, and we investigated how it is expressed and what roles it may have in primary cultures of mesenchymal cells derived from the developing tooth germ. We also examined the expression of CCN2 in a human odontogenic myxofibroma, a benign tumor of odontogenic mesenchymal origin, and considered the possible roles of CCN2 in the development of myxofibromas. Materials and methods: Mesenchymal cells of early bell‐stage tooth germs were isolated from Day‐90 bovine embryos and placed in primary culture. A resected specimen from a patient with odontogenic myxofibroma was prepared for immunohistochemical studies. Principal results: The CCN2 expression level in proliferating odontogenic mesenchymal cells freshly isolated from the early bell stage of developing bovine tooth germs and placed in primary culture was 3 times higher than that in the confluent non‐proliferating cells. Recombinant CCN2 significantly increased the proliferation and type I collagen expression in odontogenic mesenchymal cells in primary culture. Immunohistochemical analysis on myxofibroma case revealed that CCN2 was detectable in MIB‐1, a cellular marker of proliferation‐positive odontogenic mesenchymal cells adjacent to capillary blood vessels and in the endothelial cells of the vessels in the tumor. Major conclusion: CCN2 signaling would influence the proliferation of and extracellular matrix production by dental mesenchymal cells. Our results suggest that the same mechanisms of CCN2 action toward dental mesenchymal cells would also be operative in the odontogenic myxofibroma microenvironment.